Usability evaluation via accessibility design / Siti Norsazlina Haron ... [et al.] - Siti Norsazlina, Haron; Yuhainis, Abdul Talib; Abdul Hamid, Mohamed; Aida Affina, Abdul Ghani; Md. Yusof, Hamid; Azizah, Md Ajis (Universiti Teknologi MARA, Perak, 2016)
This paper provides strategies in evaluating usability via accessibility from the user experience of three replacement hospitals. The methodology refers to a five-stage evaluation process and using the “walk-through journey experience” among patient and visitors. The data analysis was based on thematic analysis principles using NVivo9. The accessibility design issues due to participant disabilities and expectation will build up for usability parameters. The findings indicate that the quality design is the positive user experience feedback on the usability of the physical design environment that fulfils their expectations and the concept of usability and accessibility is to support the user-friendly environment design.